Respiratory syncytial virus is an "opportunistic" killer. Issue 5 (20th February 2018) - Caballero, Mauricio T.; Polack, Fernando P.
Abstract: Respiratory syncytial virus (RSV), responsible for more than three million yearly hospitalizations and up to 118 000 deaths in children under 5 years, is the leading pulmonary cause of death for this age group that lacks a licensed vaccine. Ninety‐nine percent of deaths due to the virus occur in developing countries. In‐hospital RSV fatalities affect previously healthy term infants in association with bacterial sepsis, clinically significant pneumothoraxes and, to a lesser extent, comorbid conditions. Community deaths affect low‐income children from socially vulnerable families and appear to be as frequent as inpatient fatalities. In industrialized countries, RSV deaths occur almost exclusively in children with premorbid conditions. In a sense, RSV is an "opportunistic" killer. It needs a synergistic premorbid, medical practice‐related, infectious, or social co‐factor to cause a fatal outcome. But while the complex problems associated with these co‐factors await solutions, candidate vaccines, long‐lived monoclonal antibodies and antivirals against RSV are under clinical evaluation. It seems reasonable to predict that the landscape of RSV infections will look different in the next decade.